Implementasi Pembelajaran Al-Qur’an Menggunakan Metode Bil-Qolam dalam Meningkatkan Kemampuan Membaca Al-Qur’an di Asrama Nurul Ulum MAN Purworejo - Hasna, Rina Aminatul; Hamzah, Muchotob; Faisal, Vava Imam Agus (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2023)
This study aims to determine the implementation of Al-Qur’an learning using the Bil Qolam method in improving the ability to read the Qur’an at Nurul Ulum MAN Purworejo Dormitory, and to determine the supporting and inhibiting factors for implementing Al-Qur’an learning using the Bil Qolam method. In improving the ability to read the Qur’an in Nurul Ulum MAN Purworejo dormitory. The type of research used is dercriptive qualitative. The process of collecting data trough observation, interviewa, and documentation. The research results sgow that: 1) the implementation of the Bil Qolam method in improving the ability to read the Al-Qur’an at the Nurul Ulum MAN Purworejo Dormitory obtained good result, namely based on observations made by researches only 5% of student or 5 students from 54 students who have not been able to fully master the ability to read the Qur’an using the Bil Qolam method. 2) supporting factors in the application of the Bil Qolam method are the ability to read the Qur’an for students in the good category, the enthusiasm of the students, the support and motivation of the teacher, the Bil Qolam method is interesting, and can add to the insight and knowledge of the studentas. While the inhibiting factors are the atmosphere that is not conducive, students who disturb each other, and the allocation of learning time that less